Smaller Fleas: Viruses of Microorganisms - Paul Hyman; Stephen T. Abedon (Scientifica)
Life forms can be roughly differentiated into those that are microscopic versus those that are not as well as those that are multicellular and those that, instead, are unicellular. Cellular organisms seem generally able to host viruses, and this propensity carries over to those that are both microscopic and less than truly multicellular. These viruses of microorganisms, or VoMs, in fact exist as the world’s most abundant somewhat autonomous genetic entities and include the viruses of domain Bacteria (bacteriophages), the viruses of domain Archaea (archaeal viruses), the viruses of protists, the viruses of microscopic fungi such as yeasts (mycoviruses), and even the viruses of other viruses (satellite viruses). In this paper we provide an introduction to the concept of viruses of microorganisms, a.k.a., viruses of microbes. We provide broad discussion particularly of VoM diversity. VoM diversity currently spans, in total, at least three-dozen virus families. This is roughly ten families per category—bacterial, archaeal, fungal, and protist—with some virus families infecting more than one of these microorganism major taxa. Such estimations, however, will vary with further discovery and taxon assignment and also are dependent upon what forms of life one includes among microorganisms.